Cervical lymphadenopathy - Ogden, Graham (Henry Stewart Talks, 2017)
History & examination, Regional nodes, Key features of a node-investigation of a lymph node, Differential diagnosis: Infection, Malignant disease, Inflammatory disease, other causes, Likely causes based on texture, Key investigations for suspected infection and for malignant disease